2016
DOI: 10.1186/s13000-016-0520-4
|View full text |Cite
|
Sign up to set email alerts
|

Determination of GP88 (progranulin) expression in breast tumor biopsies improves the risk predictive value of the Nottingham Prognostic Index

Abstract: BackgroundThe Nottingham Prognostic Index (NPI), which combines numerical values for nodal status, tumor size and histological grade, is used in the standard of care to provide predictive value information on post-surgery survival for patients with primary breast cancer. Attempts to improve the performance of the NPI algorithm have been carried out by testing the inclusion of other biomarker expression and morphological features such as vascular invasion. In the present study, we investigated whether expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…37 Pathologic studies with 600 estrogen receptor-positive invasive ductal carcinoma cases established that high GP88 tumor score (3þ by immunohistochemistry) was associated with a 4-fold increase in recurrence and a 2.5-fold decrease in overall survival, making GP88 an independent risk of recurrence predictor and a marker for poor outcome. 42 Because GP88 is a secreted protein, EIA to measure GP88 in biological fluids demonstrated that GP88 was measurable in serum and was found at a higher level in serum of patients with BC when compared with healthy individuals. 43 Increased tumor tissue GP88 and serum levels have been found to be associated with poor outcomes in nonesmall-cell lung carcinoma, 46 and serum GP88 was associated with Gleason score and poor outcome in patients with advanced prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…37 Pathologic studies with 600 estrogen receptor-positive invasive ductal carcinoma cases established that high GP88 tumor score (3þ by immunohistochemistry) was associated with a 4-fold increase in recurrence and a 2.5-fold decrease in overall survival, making GP88 an independent risk of recurrence predictor and a marker for poor outcome. 42 Because GP88 is a secreted protein, EIA to measure GP88 in biological fluids demonstrated that GP88 was measurable in serum and was found at a higher level in serum of patients with BC when compared with healthy individuals. 43 Increased tumor tissue GP88 and serum levels have been found to be associated with poor outcomes in nonesmall-cell lung carcinoma, 46 and serum GP88 was associated with Gleason score and poor outcome in patients with advanced prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…[33][34][35][36] Both tissue and blood tests have been developed for determining GP88 expression in tumor tissue and measuring GP88 in biological fluids. Use of these tests has shown that: (1) GP88 is present in breast tumor tissue whereas it is not present in corresponding "normal" breast tissue 37 ; (2) Increased expression of GP88 in estrogen receptor-positive breast adenocarcinoma cell lines is associated with estrogen independence and resistance to anti-estrogen therapy and aromatase inhibitors, 38,39 whereas in human epidermal growth factor receptor 2overexpressing BC, GP88 stimulated human epidermal growth factor receptor 2 phosphorylation and conferred herceptin resistance 40 ; (3) Increased tumor GP88 expression measured by immunohistochemistry in breast tumor tissue is an independent predictor of recurrence and is associated with poor outcome 41,42 ; and (4) circulating levels of GP88 are measurable by enzyme immunoassay (EIA) and, compared with healthy individuals, elevated GP88 blood levels are found in patients with BC. 43 Because high GP88 tissue expression is associated with poor outcome including increased risk of recurrence and mortality and because GP88 stimulates hallmarks of metastasis, 44 we have hypothesized that GP88 circulating levels could be used in patients with MBC to monitor disease status.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 It has been demonstrated that progranulin stimulates proliferation in breast cancer cells, and progranulin was shown to mediate the mitogenic activity of estrogen by stimulating cyclin D1 expression. 13 He has reported that progranulin mediates tissue repair and tumorigenesis and these biological activities are mediated via activation of mitogen-activated protein kinase (MAPK) and phosphatidylinositol 3-kinase (PI3K) pathways. 14 However, the effects of progranulin on human colon cancer have not been reported before, and the mechnism is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…GP88 tumor tissue expression was evaluated and found to be prognostic in several studies, correlating with tumor histological grade, DFS, OS, nodal status, and tumor size. [81][82][83] Subsequently, a method to quantify circulating GP88 sandwich enzyme-linked immunosorbent assay was developed. 84 In breast cancer patients of all stages, circulating levels of GP88 were higher compared to healthy volunteers.…”
Section: Serum Gp88 As a Prognostic Marker In Early Disease And Metastatic Diseasementioning
confidence: 99%